Ответ(ы) на вопрос:
cosa=±Ö1-sin2a=(1-tg2a/2)/(1+tg2a/2)sina=±Ö1/1+ctg2a=(2tga/2)/(1+tg2a/2)cos(ab)=sinasinbcosacosbsin(a±b)=sinacosb±sinbcosatg(a+b)=sin(a+b)/cos(a+b)=(tga+tgb)/(1-tgatgb)tg(a-b)=(tga-tgb)/(1+tgatgb)ctg(a+b)=(ctgactgb-1)/(ctga+ctgb)ctg(a-b)=(ctgactgb+1)/(ctgb-ctga)sin2a=2sinacosa=(2tga)/(1+tg2a)cos2a=cos2a-sin2a=(1-tg2a)/(1+tg2a)=2cos2a-1=1-2sin2atg2a=2tga/(1-tg2a) ctg2a=(ctg2a-1)/2ctgactg2a=(ctg2a-1)/2ctgacos2a/2=1+cosa/2 cos2a=(1+cos2a)/2sin2a/2=1-cosa/2 sin2a=(1-cos2a)/2cosa/2=±Ö1+cosa/2sina/2=±Ö1-cosa/2tga/2=±Ö1-cosa/1+cosa=(sina)/(1+cosa)=(1-cosa)/sinactga/2=±Ö1+cosa/1-cosa=sina/(1-cosa)=(1+cosa)/sinasina+cosa=Ö2 cos(P/4-a)sina-cosa=Ö2 sin(a-P/4)cosa-sina=Ö2 sin(P/4-a)cosa+cosb=2cos(a+b)/2cos(a-b)/2cosa-cosb=-2sin(a+b)/2sin(a-b)/2sina+sinb=2sin(a+b)/2cos(a-b)/2sina-sinb=2sin(a-b)/2cos(a+b)/2tga±tgb=(sin(a±b))/cosacosbcosacosb=1/2(cos(a-b)+cos(a+b))sinasinb=1/2(cos(a-b)-cos(a+b))sinacosb=1/2(sin(a+b)+sin(a-b))tga=(2tga/2)/(1-tg2a/2)
cosa=±Ö1-sin2a=(1-tg2a/2)/(1+tg2a/2)sina=±Ö1/1+ctg2a=(2tga/2)/(1+tg2a/2)cos(ab)=sinasinbcosacosbsin(a±b)=sinacosb±sinbcosatg(a+b)=sin(a+b)/cos(a+b)=(tga+tgb)/(1-tgatgb)tg(a-b)=(tga-tgb)/(1+tgatgb)ctg(a+b)=(ctgactgb-1)/(ctga+ctgb)ctg(a-b)=(ctgactgb+1)/(ctgb-ctga)sin2a=2sinacosa=(2tga)/(1+tg2a)cos2a=cos2a-sin2a=(1-tg2a)/(1+tg2a)=2cos2a-1=1-2sin2atg2a=2tga/(1-tg2a) ctg2a=(ctg2a-1)/2ctgactg2a=(ctg2a-1)/2ctgacos2a/2=1+cosa/2 cos2a=(1+cos2a)/2sin2a/2=1-cosa/2 sin2a=(1-cos2a)/2cosa/2=±Ö1+cosa/2sina/2=±Ö1-cosa/2tga/2=±Ö1-cosa/1+cosa=(sina)/(1+cosa)=(1-cosa)/sinactga/2=±Ö1+cosa/1-cosa=sina/(1-cosa)=(1+cosa)/sinasina+cosa=Ö2 cos(P/4-a)sina-cosa=Ö2 sin(a-P/4)cosa-sina=Ö2 sin(P/4-a)cosa+cosb=2cos(a+b)/2cos(a-b)/2cosa-cosb=-2sin(a+b)/2sin(a-b)/2sina+sinb=2sin(a+b)/2cos(a-b)/2sina-sinb=2sin(a-b)/2cos(a+b)/2tga±tgb=(sin(a±b))/cosacosbcosacosb=1/2(cos(a-b)+cos(a+b))sinasinb=1/2(cos(a-b)-cos(a+b))sinacosb=1/2(sin(a+b)+sin(a-b))tga=(2tga/2)/(1-tg2a/2)
Не нашли ответ?
Похожие вопросы